PKA preperation of some diimines acids derived from benzil - Khaleel Al-Nuami; Mahmood Saeed; Adel Azooz (College of Education for Pure Sciences, 2005)
The study is concerned with the preparation of four acids having diimines in a forms of Schiff bases as well as oxime in the same molecule. The acids prepared are identified by using UV, IR, NMR and melting points. The main object of the study is the determination of pKa of organic diimine acids under investigation, using a potentiometric method. It is confirmed in this study, that the1'potentiometric method is simple, fast, with an accuracy of ± 0.001 pKa unit and can be applied to more than one titrable proton in the molecule. The study shows that acidities of oxime benzilnylidenes having phenolic groups in o,m and p-positions is depend on donor-acceptor properties of oxime group. Also the acidity of oxime benzilnylidene-2-amino aniline is greater than the aliphatic amine. الخلاصة